Factors influencing timely initiation and completion of gestational diabetes mellitus screening and diagnosis - a qualitative study from Tamil Nadu, India - Nielsen, Karoline Kragelund (BMC Pregnancy Childbirth, 2017)
BACKGROUND: In 2007, universal screening for gestational diabetes mellitus (GDM) was introduced in Tamil Nadu, India. To identify factors hindering or facilitating timely initiation and completion of the GDM screening and diagnosis process, our study investigated how pregnant women in rural and urban Tamil Nadu access and navigate different GDM related health services. METHODS: The study was carried out in two settings: an urban private diabetes centre and a rural government primary health centre. Observations of the process of screening and diagnosis at the health centres as well as semi-structured interviews with 30 pregnant women and nine health care providers were conducted. Data was analysed using qualitative content analysis. RESULTS: There were significant differences in the process of GDM screening and diagnosis in the urban and rural settings. Several factors hindering or facilitating timely initiation and completion of the process were identified. Timely attendance required awareness, motivation and opportunity to attend. Women had to attend the health centre at the right time and sometimes at the right gestational age to initiate the test, wait to complete the test and obtain the test report in time to initiate further action. All these steps and requirements were influenced by factors within and outside the health system such as getting right information from health care providers, clinic timings, characteristics of the test, availability of transport, social network and support, and social norms and cultural practices. CONCLUSIONS: Minimising and aligning complex stepwise processes of prenatal care and GDM screening delivery and attention to the factors influencing it are important for further improving and expanding GDM screening and related services, not only in Tamil Nadu but in other similar low and middle income settings. This study stresses the importance of guidelines and diagnostic criteria which are simple and feasible on the ground. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12884-017-1429-y) contains supplementary material, which is available to authorized users.